2004
DOI: 10.1128/iai.72.9.4985-4995.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptococcal Yeast Cells Invade the Central Nervous System via Transcellular Penetration of the Blood-Brain Barrier

Abstract: Cryptococcal meningoencephalitis develops as a result of hematogenous dissemination of inhaled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
220
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(234 citation statements)
references
References 44 publications
14
220
0
Order By: Relevance
“…These results support the hypothesis that C. neoformans traverses the blood-brain barrier following a "transcellular pathway." A scanning electron microscopic study has shown that microvilli and membrane extension embraced C. neoformans during its internalization, suggesting that C. neoformans invasion of HBMEC utilizes a "zipper-like mechanism" in which the host cell plasma membrane enwraps the invading yeast (36). This mechanism therefore requires C. neoformans cell-induced HBMEC cytoskeletal rearrangements to accumulate actin fibers at the site of C. neoformans entry.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the hypothesis that C. neoformans traverses the blood-brain barrier following a "transcellular pathway." A scanning electron microscopic study has shown that microvilli and membrane extension embraced C. neoformans during its internalization, suggesting that C. neoformans invasion of HBMEC utilizes a "zipper-like mechanism" in which the host cell plasma membrane enwraps the invading yeast (36). This mechanism therefore requires C. neoformans cell-induced HBMEC cytoskeletal rearrangements to accumulate actin fibers at the site of C. neoformans entry.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, infected macrophage cells may travel widely throughout the host circulatory and lymphatic systems, where they interact intimately with one another and with other cell types through transient contacts [12]. We speculate that internalised C. neoformans may use such transient contact in order to cross the blood-brain barrier by direct cell-to-cell spread from adherent infected macrophages to microvascular endothelial cells [14]. In fact, spreading from macrophages to other cell types during dissemination has been demonstrated for other pathogens in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Two different studies have found Cr. neoformans cells inside of brain endothelial cells in mice infected intravenously with live organisms [40,41]. Thus, Cr.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…neoformans with endothelial cells has also been analyzed in vitro. Both encapsulated and unencapsulated organisms are able to induce their own endocytosis by brain microvascular endothelial cells [41,42]. The organisms induce membrane ruffling and projection of microvilli that surround the organisms and pull them into the cell.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%